Breast implant-associated anaplastic large cell lymphoma: A review and assessment of cutaneous manifestations - N. Shahriari, MD; K. Ferenczi, MD; P.W. Heald, MD (Wolters Kluwer, 2017)
One newly recognized form of T-cell lymphoma is breast implant-associated anaplastic large cell lymphoma (biALCL), which appears in close proximity to breast implants. The number of reported cases of biALCL is increasing and warrants careful attention by clinicians to more effectively diagnose and treat affected individuals.As pertinent to dermatologists, the objective of this paper is to present the associated cutaneous features of this clinical entity along with the pathogenesis, management, and clinical outcomes.biALCL is a T-cell lymphoma in which malignant T-cells are characterized by large pleomorphic and anaplastic morphology and immunoreactivity for CD30, similar to primary cutaneous anaplastic large cell lymphomas (pcALCL). It has a favorable clinical outcome like nonimplant-associated pcALCL and involves the fibrous capsule around the implant, which creates an immunologically privileged site with a peri-implant effusion (seroma). More rare presentations are of a solitary mass.Appropriate management of biALCL is the complete surgical removal of the implant and total capsulectomy. Dermatologists should be aware of the occurrence of this entity in patients who have breast implants because patients may present specifically for breast-related cutaneous findings or have incidental cutaneous changes noted during a skin examination.The recognition and timely diagnosis of biALCL is critical to prevent progression to more advanced disease, ensure adequate treatment with removal of the implant, and avoid unnecessary aggressive systemic chemotherapy. Keywords: Breast implants, T-cell lymphoma, anaplastic large cell lymphoma, cutaneous manifestations, pathogenesis, management